Unpacking the beast of burden: Joerges on the constitutional, political, and epistemological baggage of European integration - Turkuler Isiksel (European Law Open)
Christian Joerges is a scholar whose work spills over the conventional boundaries between public and private law, social science and legal theory, law and public policy, empirical inquiry and normative philosophy. This essay brings into focus Joerges’s under-appreciated role as a prescient, critical intellectual biographer of European integration. It argues that Joerges’s work has helped to diagnose, explain, and dismantle three misconceptions or myths with which European integration has been saddled from its formative decades. These misconceptions are (1) that the European integration project is ‘self-legitimating’ and therefore politically neutral; (2) that the delegation of decision-making authority to supranational institutions is constitutionally neutral; and (3) that there can be an epistemologically neutral, authoritative disciplinary perspective from which to comprehend European integration. Breaking the hold of these misconceptions is an essential step towards gaining a critical understanding of the promises and limitations of European integration today.